2020
DOI: 10.7554/elife.57000
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular sorting of neuregulins controls the assembly of excitatory-inhibitory cortical circuits

Abstract: The assembly of specific neuronal circuits relies on the expression of complementary molecular programs in presynaptic and postsynaptic neurons. In the cerebral cortex, the tyrosine kinase receptor ErbB4 is critical for the wiring of specific populations of GABAergic interneurons, in which it paradoxically regulates both the formation of inhibitory synapses as well as the development of excitatory synapses received by these cells. Here, we found that Nrg1 and Nrg3, two members of the neuregulin family of troph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Double immunofluorescence assays demonstrated a virtual complete co-localization between Af450, and Af380-immunoreactivities, but more importantly, both antibodies produced intense immunoreactivity largely restricted to axonal fibres and presynaptic-like puncta with an excellent signal-to-noise relationship in rat brain cortical sections, and the signals were virtually abolished by peptide preadsorption. This is consistent with several studies that showed a similar CB 1 immunoreactivity distribution profile using antibodies raised against C-terminal end fragments of variable length, including peptides comprising the last 13 (Egertová and Elphick 2000), 15 (Bodor et al 2005;Deshmukh et al 2007;Eggan and Lewis 2007;Eggan et al 2010) and 73 (Hájos et al 2000;Wager-Miller et al 2002;Harkany et al 2003;Monory et al 2006;Eggan and Lewis 2007) C-terminal end residues, as well as a number of reports using Af380 (Lafourcade et al 2007;Yoneda et al 2013;Diniz et al 2019;Fuerte-Hortigón et al 2021) and Af450 (Yoneda et al 2013;Rivera et al 2015;Exposito-Alonso et al 2020) antibodies in the rodent brain cortex. Moreover, both Af380 (Mateo et al 2017) and Af450 (Lafourcade et al 2007;Peñasco et al 2020;Egaña-Huguet et al 2021) antibodies have proven to be adequate to describe the ultrastructural distribution of CB 1 receptors and have been validated for specificity in transgenic mice lacking CB 1 receptor (Hebert-Chatelain et al 2014b;Remmers et al 2017;Gutiérrez-Rodríguez et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Double immunofluorescence assays demonstrated a virtual complete co-localization between Af450, and Af380-immunoreactivities, but more importantly, both antibodies produced intense immunoreactivity largely restricted to axonal fibres and presynaptic-like puncta with an excellent signal-to-noise relationship in rat brain cortical sections, and the signals were virtually abolished by peptide preadsorption. This is consistent with several studies that showed a similar CB 1 immunoreactivity distribution profile using antibodies raised against C-terminal end fragments of variable length, including peptides comprising the last 13 (Egertová and Elphick 2000), 15 (Bodor et al 2005;Deshmukh et al 2007;Eggan and Lewis 2007;Eggan et al 2010) and 73 (Hájos et al 2000;Wager-Miller et al 2002;Harkany et al 2003;Monory et al 2006;Eggan and Lewis 2007) C-terminal end residues, as well as a number of reports using Af380 (Lafourcade et al 2007;Yoneda et al 2013;Diniz et al 2019;Fuerte-Hortigón et al 2021) and Af450 (Yoneda et al 2013;Rivera et al 2015;Exposito-Alonso et al 2020) antibodies in the rodent brain cortex. Moreover, both Af380 (Mateo et al 2017) and Af450 (Lafourcade et al 2007;Peñasco et al 2020;Egaña-Huguet et al 2021) antibodies have proven to be adequate to describe the ultrastructural distribution of CB 1 receptors and have been validated for specificity in transgenic mice lacking CB 1 receptor (Hebert-Chatelain et al 2014b;Remmers et al 2017;Gutiérrez-Rodríguez et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Here we performed a F4P-based analysis of the specificity of five representative commercial anti-CB 1 antibodies designed against N-and C-terminal regions of CB1 receptor (hereinafter referred to as N-and C-terminal antibodies) and selected on the basis of the sequences against which they were generated, which can determine the final outcome in different end-use applications. This included two N-terminal and one C-terminal antibodies from Santa Cruz Biotechnology, which have been discontinued and replaced by other antibodies probably due to low demand, and two polyclonal antibodies raised in goat and rabbit against the 31 amino acids at the extreme carboxy-terminus (C-terminus) of CB 1 receptor, which have been widely used in the last decade (Yoneda et al 2013;Rivera et al 2015;Rodríguez-Cueto et al 2016;Mateo et al 2017;Puighermanal et al 2017;Rhomberg et al 2018;Diniz et al 2019;Puente et al 2019;Uchigashima et al 2020;Exposito-Alonso et al 2020;Peñasco et al 2020;Egaña-Huguet et al 2021;Fuerte-Hortigón et al 2021) and validated for some applications using different transgenic mice models lacking CB 1 receptor, either completely or in specific cell phenotypes or subcellular compartments (Hebert-Chatelain et al 2014a;Remmers et al 2017;Gutiérrez-Rodríguez et al 2018). To this end, our workflow combined commonly accepted testing and validation approaches along with pharmacological assays to confirm or rule out the presence of CB 1 receptor in samples yielding CB 1 -like immunoreactive bands on Western blot.…”
Section: Introductionmentioning
confidence: 99%
“…To examine how TrkB affects excitatory synapses on PV neurons, we stained and quantified the Homer1‐positive synapses that were present on the PV cell bodies. We applied a threshold on both PV‐Tomato and the Homer1 signals and measured the intensity, size, and density of Homer1 punctae that were within the boundary of the PV cell body, similar to a previously published method (Exposito‐Alonso et al, 2020). On average, there were ~28 Homer1+ synapses on each PV cell body.…”
Section: Resultsmentioning
confidence: 99%
“…and measured the intensity, size, and density of Homer1 punctae that were within the boundary of the PV cell body, similar to a previously published method(Exposito-Alonso et al, 2020). On average, there were ~28 Homer1+ synapses on each PV cell body.…”
mentioning
confidence: 99%
“…Moreover, Erbb4 null mutant mice display lower numbers of PV+ interneurons and compromised GABA release [ 194 ]. Previous studies have shown that ErbB4 deficits impair the correct wiring of cortical neurons, affecting excitatory synapses between pyramidal neurons and PV+ cells [ 192 , 195 ], suggesting that the NRG1 receptor plays a critical role in excitatory/inhibitory circuit homeostasis.…”
Section: Genetic Modelsmentioning
confidence: 99%